RISK FACTOR OF ACTIVITY LEVEL AND NUTRITIONAL CONSUMTION PATTERN WITH INCIDENCE OF TYPE 2 DIABETES MELLITUS in Sanglah Hospital Denpasar - I Nyoman Dharma Wiasa; Luh Seri Ani; Pande Putu Januraga (Stikes Wira Medika Bali, 2017)
Diabetes mellitus is a degenerative disease that has an increasing prevalence worldwide and Indonesia. In Bali, the prevalence is 5.9% of the total population. This number will continue to increase as the change of lifestyle and eating pattern in the community. This study aims to prove the risk factors that related to the incident of type 2 diabetes mellitus in out clinic patient of Sanglah Hospital.This was an observational analytic study using unmatched case control study. The respondents in this study consisted of case and control with 1:2 ratio. Case was type 2 DM outpatients that matched diagnostic criteria or type 2 DM patients that had been treated and visited Sanglah hospital. Control was non diabetic outpatients that came to sanglah hospital. The number of respondents was 84 respondent that were determined using consecutive sampling.The instruments were questioners, medical records, and fasting blood sugar levels. Univariate, bivariate (chi-square) and multivariate (multiple logistic regression) analysis were used in this study. The result of this study showed the OR value of activity levels was 4.298 (95% CI = 1.646 – 11.226. The OR value of fat consumtion patterns was 7.171 (95% CI=1.986-11.226). The OR of karbohidrat consumtion was 0.224 (95% CI: 0.071-0.703). The result also showed that fat consumtion pattern had a chance to cause diabetic by 6.7 compared to activity levconsumtion of carbohidrat to cure diabetes at Sanglah Hospital, Denpasar.The health institutions should improve promotive and preventive measures to diabetic and non diabetic patients.